D crop protection Malaysia: competition from generic herbicides - Foong, Soon Yau; Ho, Beng Seng (Emerald Group Publishing, 2011)
Case overview: This case illustrates how emergence of generic products had threatened the survival of DCPM and forced its management to urgently review the company's existing approach to pricing of its main herbicide product. The case presents opportunities for readers to discuss the deficiencies of DCPM's existing product costing approach and recommend modifications to meet the price and gross profit margin targets specified. It also highlights issues relating to supply chain management and human resource practices that might have to be improved to enhance DCPM's long‐term competitiveness. Expected learning outcomes: To understand the effects of globalisation and emergence of generic products on intensity of market competition for branded products. To identify deficiencies of the current product costing system of DCPM for pricing decision. To apply alternative contemporary approach to product costing and pricing of Metrix and the other value‐added services. To identify measures to enhance supply chain management and inventory management in DCPM. To assess DCPM's human resources practices. To evaluate the effectiveness of DCPM's existing competitive strategy and formulate new competitive strategy to sustain DCPM's long‐term competitiveness.